Β‐Hydroxybutyric acid attenuates heat stress‐induced neuroinflammation via inhibiting TLR4/p38 MAPK and NF‐κB pathways in the hippocampus. Issue 4 (25th March 2022) - Huang, Jian; Chai, Xuejun; Wu, Yongji; Hou, Yan; Li, Cixia; Xue, Yuhuan; Pan, Jiarong; Zhao, Yongkang; Su, Aimin; Zhu, Xiaoyan; Zhao, Shanting
Abstract: Heat stress causes many pathophysiological responses in the brain, including neuroinflammation and cognitive deficits. β‐Hydroxybutyric acid (BHBA) has been shown to have neuroprotective effects against inflammation induced by lipopolysaccharide. The aim of the present study was to evaluate the effects of BHBA on neuroinflammation induced by heat stress, as well as the underlying mechanisms. Mice were pretreated with vehicle, BHBA or minocycline (positive control group) and followed by heat exposure (43°C) for 15 min for 14 days. In mice subjected to heat stress, we found that treatment with BHBA or minocycline significantly decreased the level of serum cortisol, the expressions of heat shock protein 70 (HSP70), and the density of c‐Fos + cells in the hippocampus. Surprisingly, the ethological tests revealed that heat stress led to cognitive dysfunctions and could be alleviated by BHBA and minocycline administration. Further investigation showed that BHBA and minocycline significantly attenuated the activation of microglia and astrocyte induced by heat stress. Pro‐inflammatory cytokines were attenuated in the hippocampus by BHBA and minocycline treatment. Importantly, compared with the heat stress group, mice in the BHBA treatment group and positive control group experienced a decrease in the expressions of toll‐like receptor 4 (TLR4), phospho‐p38 (p‐p38), and nuclear factor kappa B (NF‐κB). Our results elucidated that BHBA inhibits neuroinflammation induced by heat stress by suppressing the activation of microglia and astrocyte, and modulating TLR4/p38 MAPK and NF‐κB pathways. This study provides new evidence that BHBA is a potential strategy for protecting animals from heat stress.